Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus - Mita, Toshiharu; Olmi, Massimo (Zootaxa, 2018)
Ampulicomorpha thauma Rasnitsyn & Matveev (Hymenoptera: Embolemidae) and Sclerogibba rossi Olmi (Hymenoptera: Sclerogibbidae) were newly recorded from Japan. Females of Embolemus walkeri Westwood were found in the soil together with nymphs of Cixiidae. Trogloembolemus okanoi sp. nov. is described and illustrated. The holotype ♀ was collected in the soil at a depth of one meter. A key to species of Japanese Embolemidae was updated.